Praktek Tabarruk di Pondok Pesantren Musthafawiyah Terhadap Tafsir Al-Quran Surah Al-A’raf Ayat 96 - Hidayat, Rahmad; Ardiansyah (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This research aims to analyse the practice of tabarruk in Pondok Pesantren Musthafawiyah, especially the interpretation of Surah Al-A'raf verse 96. Tabarruk, which is an effort to get closer to Allah by seeking blessings through certain objects, places or individuals, is often practised in religious and spiritual contexts. Through a descriptive qualitative approach, this study identifies how the interpretation of Surah Al-A'raf verse 96 is interpreted by the caregivers and students of Pondok Pesantren Musthafawiyah in relation to the practice of tabarruk. This verse talks about the importance of belief and practice in obtaining blessings from Allah, and how it is applied in daily life in pesantren. The results showed that the interpretation used leads to the understanding that true blessings are only obtained through faith and good deeds, although the practice of tabarruk is still seen as a way to get closer to Allah if done in accordance with the principles of sharia. This research is expected to provide a deeper understanding of the relationship between the practice of tabarruk and the interpretation of the Qur'anic text in the context of pesantren.